STEEL CIRCULAR ECONOMY IN THE CIVIL CONSTRUCTION: A STUDY CASE OF STEEL INDUSTRY - Clarissa Sena de Andrade; Alberto Casado Lordsleem Júnior; Emanoel Silva de Amorim; Girlândia de Morais Sampaio Girlândia de Morais Sampaio; Diogo Cavalcanti Oliveira Diogo Cavalcanti Oliveira; Joaquin Humberto Aquino Rocha (Mix Sustentável, 2023)
This research aims to describe a case study of the application of the circular economy of steel in a steel industry, demonstrating the impacts on economic, social and environmental sustainability. The methodology employed included a case study with stages of literature review, field investigation and analysis of collected data. The results demonstrated the positive impacts of the business model in the context of the circular economy, with the reduction of greenhouse gas emissions by approximately 50% compared to the global average; 8.90% reduction in energy spent during steel manufacturing from 2019 to 2020, despite the 5.53% increase in production in the year. It should be noted that each year a greater percentage of waste is reused, with a maximum value of 78.88% in 2020. The main contribution of this work consists in the systematization of the actions that characterize the circular economy in the steel industry, through which it encourages sustainable processes in the civil construction industry, The sector can be one of the drivers of the transition to a circular economy by reducing the consumption of raw materials and energy, in addition to greenhouse gas emissions, increasing profitability and having a sustainable approach.